AUSÊNCIA DE INIBIDORES DE PCR NA DETECÇÃO DE SOJA TRANSGÊNICA - ARISI, ANA C. M.; DINON, ANDRÉIA Z.; FIORENTINI, ANGELA M.; BROD, FÁBIO C. A.; FAGUNDES, GILBERTO A. (Salão do Conhecimento, 2013)
Resumo